Acute Retropharyngeal Abscess in Libyan Children: Case Series and Literature Review - Alougly, Shirin; Alhsony, Alia; Elarwah, Aisha; Elbragathy, Suliman (Ibnosina Journal of Medicine and Biomedical Sciences, 2022)
Background A retropharyngeal abscess (RPA) is a deep neck infection that considers a medical emergency because of the possibility of serious complications including life-threatening upper airway obstruction, mediastinitis, and sepsis.Materials and Methods We present our experience in Benghazi Children's Hospital, describing the clinical presentations, diagnostic workup, management, and the outcome of four children presented during the time period between November 2017 and November 2021 as cases of RPA secondary to penetrating trauma to the posterior pharyngeal wall either due to ingestion of a foreign body or due to manipulation of tonsils by the traditional therapist.Results All cases presented with fever, poor feeding, and hyperextension of the neck. All were diagnosed by ultrasound and they needed surgical drainage of RPA, as they did not improve with medical treatment alone.Conclusion A high index of suspicion is necessary for the early diagnosis and treatment of RPA. Two of our cases were presented following the manipulation of tonsils by a traditional therapist, so we attempted to emphasize this life-threatening consequence after traditional therapy, as well as the unnecessary morbidity and mortality associated with this ongoing traditional treatment in our country.
Keywords: retropharyngeal abscess; children